Designing an Appointment Management System for the Mother and Child Health Department of the Klinik Kesihatan Changlun - Ali A, Alghamedi Ahmad (2011)
Information and Communication Technology has been changing the way things have been carried out. Traditionally many work required people to visit the location where the work has been carried out. ICT has been making these services available at their fingertips by hosting these applications online. Klinik Kesihatan Changlun is a public general clinic in the state of Kedah. The appointment management which is one of the most important services of a clinic is presently carried out manually here. Both patients and the staff have to face a lot of problems due to the inefficiency of the manual system. If the system can be automated and made available on the internet, it will solve a lot of problems currently faced by them. This project proposes to design an appointment management system for the Mother and Child Health Department of the Klinik Kesihatan Changlun. The project has been proposed to follow the formal research methodology proposed by Kuchler and Vaishnavi due to its suitability for small to medium sized development projects. Finally it has been proposed conduct a usability test on the prototype developed for ease of use and user friendliness with the aid of the questionnaire.